Association between urinary sodium excretion and hard outcomes in non-dialysis chronic kidney disease patients - Cury, Cecília Malheiro [UNESP]; Banin, Vanessa Burgugi [UNESP]; dos Reis, Pamela Falbo [UNESP]; Caramori, Jacqueline Costa Teixeira [UNESP]; Barretti, Pasqual [UNESP]; de Andrade, Luís Gustavo Modelli [UNESP]; Martin, Luis Cuadrado [UNESP] (Springer Nature, 2022)
Background: Restriction of sodium intake is routinely recommended for patients with chronic kidney disease (CKD). Whether or not sodium intake is associated with the progression of CKD and mortality remains uncertain. We evaluated the association between urinary sodium excretion (as a surrogate for sodium intake) with the occurrence of renal failure and mortality in patients with non-dialytic CKD. Methods: We conducted a retrospective study of patients followed at a CKD clinic care hospital from October 2006 to March 2017. Adult patients with non-dialytic CKD were included. Using a time-to-event analysis, we examined the association of urinary sodium excretion as a categorical variable (categorized as quintiles: 1st quintile: 0.54–2.51 g; 2nd quintile: 2.52–3.11 g, 3rd quintile: 3.12–3.97 g, 4th quintile: 3.98–5.24 g and 5th quintile: 5.26–13.80 g) and the outcomes of interest. The primary outcome was defined as progression to end-stage renal disease requiring any type of renal replacement therapy. The secondary outcome was mortality. Results: Two hundred five patients were included in the study (mean follow up of 2.6 years) with a mean eGFR of 26 (19–41) ml/min/1.73m2. 37 patients (18%) required renal replacement therapy and 52 (25,3%) died. There was association between urinary sodium excretion and need for renal replacement therapy (adjusted HR 0.245; 95%CI 0.660–0.912). There was no association between urinary sodium excretion and mortality in adjusted models. Conclusion: Moderate sodium intake was associated with a lower risk of renal failure.
Keywords: Chronic kidney disease; Renal failure; Sodium intake; Urinary sodium excretion